The Role of Entrepreneurship Courses in Shaping Students' Business Character and Interests in the Digital Era (Case Study of STIMI YAPMI Makassar Students Class of 2023) - Adrianah Adrianah; Rukmana Sari; Yusra Nginang; Siti Hawania (PT. Maju Malaqbi Makkarana, 2026)
This research aims to analyze the role of the Entrepreneurship Course (MK) in shaping entrepreneurial character and fostering business interest in STIMI YAPMI Makassar Class of 2023 students in the midst of the challenges of the digital era. The research method used was qualitative descriptive with data collection techniques through observation, interviews, and questionnaires of 30 respondents. The results of the study show that MK Entrepreneurship makes a significant contribution (90%) in increasing self-efficacy and student courage in taking business risks. In the context of interest, as many as 83% of respondents stated that they were interested in building a digital-based business, especially through social commerce platforms and digital resellers. However, the main obstacles found are limited financial capital and the need for technical assistance related to advanced digital marketing. In conclusion, entrepreneurship education at STIMI YAPMI Makassar has succeeded in building a strong character foundation, but it is necessary to strengthen the business incubation aspect so that students' interests can be realized into sustainable business units.